PENGARUH TOTAL ASET, DANA PIHAK KETIGA, DAN KREDIT PADA BANK UMUM TERHADAP PERTUMBUHAN EKONOMI PROVINSI-PROVINSI DI INDONESIA PADA TAHUN 2013-2016 - Lutfi Nofi Zumaidah; Aris Soelistyo (Program Studi Ekonomi Pembangunan, 2018)
The increased economic growth cannot be separated from the role of banks in providing financial services because almost all financial activities require bank services. This research aims to determine the influences of total assets, third-party fund, and credit to commercial banks on economic growth of Indonesia in 2013 – 2016. Data used in this research is panel data in 2013 until 2016 year period. The method of analysis used in this research is multiple linear regression analysis using panel data. The result shows that total assets (X1) have significant positive influence on economic growth with coefficient value 0.175711 and probability value 0.0075. Third-Party Fund Value (X2) has positive and significant influence on economic growth with coefficient value 0.285815 and probability value 0.0000.Value of Credit (X3) has significant positive influence on economic growth with coefficient value 0.088468 and probability value 0.0023.Keywords: Economic Growth, Total Assets, Third-Party Fund, Credit